MiR‐212 downregulation contributes to the protective effect of exercise against non‐alcoholic fatty liver via targeting FGF‐21. Issue 2 (9th December 2015) - Xiao, Junjie; Bei, Yihua; Liu, Jingqi; Dimitrova‐Shumkovska, Jasmina; Kuang, Dapeng; Zhou, Qiulian; Li, Jin; Yang, Yanning; Xiang, Yang; Wang, Fei; Yang, Changqing; Yang, Wenzhuo
Abstract: Non‐alcoholic fatty liver disease (NAFLD) is associated with obesity and lifestyle, while exercise is beneficial for NAFLD. Dysregulated microRNAs (miRs) control the pathogenesis of NAFLD. However, whether exercise could prevent NAFLD via targeting microRNA is unknown. In this study, normal or high‐fat diet (HF) mice were either subjected to a 16‐week running program or kept sedentary. Exercise attenuated liver steatosis in HF mice. MicroRNA array and qRT‐PCR demonstrated that miR‐212 was overexpressed in HF liver, while reduced by exercise. Next, we investigated the role of miR‐212 in lipogenesis using HepG2 cells with/without long‐chain fatty acid treatment (±FFA). FFA increased miR‐212 in HepG2 cells. Moreover, miR‐212 promoted lipogenesis in HepG2 cells (±FFA). Fibroblast growth factor (FGF)‐21, a key regulator for lipid metabolism, was negatively regulated by miR‐212 at protein level in HepG2 cells. Meanwhile, FFA downregulated FGF‐21 both at mRNA and protein levels in HepG2 cells. Also, FGF‐21 protein level was reduced in HF liver, while reversed by exercise in vivo . Furthermore, siRNA‐FGF‐21 abolished the lipogenesis‐reducing effect of miR‐212 inhibitor in HepG2 cells (±FFA), validating FGF‐21 as a target gene of miR‐212. These data link the benefit of exercise and miR‐212 downregulation in preventing NAFLD via targeting FGF‐21.